Workplace incivility and its effect on performance: A study of the Kumasi Metropolitan Assembly - Akomeah Gyamfi, Irene (2015)
A thesis submitted to the Department of Managerial Sciences, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration (Human Resource Management option).